Pathophysiology of the relationship of psoriasis and metabolic disorders - Owczarczyk-Saczonek, Agnieszka; Nowicki, Roman (Dermatology Review/Przegląd Dermatologiczny, 2013)
Many recent epidemiological studies have shown frequent coexistence of metabolic disturbances (insulin resistance, atherogenic dyslipidemia, hypertension and cardiovascular diseases) especially in patients with severe psoriasis. Psoriasis and atherosclerosis have a similar pathomechanism related to the conception of psoriatic march. The same cytokines (TNF-α, IL-6, IL-17) and lymphocytes (Th1, Th17) play an important role in these disorders. In addition, in both processes similar endothelial dysfunction and oxidative stress are observed. Almost twice as high obesity occurrence in patients with psoriasis is the source of metabolically active adipokines, which correlate with the severity of the disease and influence the development of metabolic disorders. These observations show that psoriasis is a systemic inflammatory process and dermatologists should not only treat skin lesions, but also diagnose and monitor coexisting disturbances, in order to prevent the development of associated metabolic disorders.